If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -3y + -5x + 13y = 0 Reorder the terms: 10x + -5x + -3y + 13y = 0 Combine like terms: 10x + -5x = 5x 5x + -3y + 13y = 0 Combine like terms: -3y + 13y = 10y 5x + 10y = 0 Solving 5x + 10y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10y' to each side of the equation. 5x + 10y + -10y = 0 + -10y Combine like terms: 10y + -10y = 0 5x + 0 = 0 + -10y 5x = 0 + -10y Remove the zero: 5x = -10y Divide each side by '5'. x = -2y Simplifying x = -2y
| 10xsquare-3x-1=0 | | 2p-(-86)=52 | | 3600=200x-x^2 | | -4l+(-25)=55 | | 3x-13y=2forwhy | | 4(x-2)+2x=3(x-1)-11 | | -3e-72=-18 | | -214+-8(2x-3)=-334 | | 3v-36=-42 | | 10x+5=12y+5 | | 15y+20= | | 4r+(-12)=48 | | 15y/4=90 | | 2x-6+4x+28=6x+22 | | 3(x+1)x+4(x+3)=22 | | 4(2x-y)=2y+5 | | 147.1875=3r(3.14r^2) | | 0.4(x+25)-3=0.2(7x+10) | | 13x-4x=-63 | | 3y+4z=9fory | | 8x=6y+5 | | 22-6y+y^2-14=0 | | 83=15+2(x) | | -8a=-8b | | (3)(2x-4)+2(2x-4)-x=-17 | | 12=15*Z-1/5 | | x+(-40)=y | | X^2+4x-62.5=0 | | 15=5+9(3) | | b+-4=-4 | | -5x=-5y | | g/3-0.9=-.4 |